Properties of Cellulose Sheets Modified with Potassium-Humate and Copper (II)-Sulfate - Tóth, Annamária; Halász, Katalin (International Journal of Engineering and Management Sciences, 2019)
Throughout our research we have made potassium-humate from brown coal of Dudar. With potassiumhumate and copper(II)-sulfate we made test sheets of linter cellulose fibers. The surface energy, surface wettability, CIE Lab color-coordinates changing, bending resistance and tensile strength of the produced test sheets has been examined. There was no big difference in the different samples during surface energy and wettability testing. Examination of mechanical properties suggests that potassium-humate content increases bending resistance of the test sheets. The bending resistance of samples increased by 32%, 100% and 336% compared to the control test sheets while adding potassium-humate.